Clinicopathological evaluation of 100 cases of mucinous carcinoma of breast with emphasis on axillary staging and special reference to a micropapillary pattern. Issue 12 (20th October 2010) - Ranade, Aditi; Batra, Rashmi; Sandhu, Gagangeet; Chitale, Rohit A; Balderacchi, Jasminka
Abstract : Background: Pure mucinous breast carcinoma (PMBC) is uncommon and associated with better prognosis than mixed mucinous breast carcinoma (MMBC). A micropapillary pattern in PMBC has been identified although its prognostic significance is questionable. Methods: A retrospective review of 100 cases of mucinous carcinoma diagnosed between 2000 and 2009 was conducted. Two broad categories were studied: PMBC (more than 90% mucinous component; n=45) and MMBC (less than 90% mucinous component; n=55). PMBC was further subclassified as hypocellular/type A (n=37) and cellular/type B (n=8). Receptor status, clinicomorphological and prognostic features were compared without patient follow-up. Results: Mean age at diagnosis in PMBC and MMBC was 60 and 63 years, while mean tumour size was 1.65 and 2.5 cm, respectively. Mean age in type A and type B PMBC patients was 75 and 55 years, respectively. The majority of PMBCs were well differentiated, with two poorly differentiated cases as well. The majority of MMBCs were moderately differentiated. A micropapillary pattern was seen in 20% of PMBCs. Sentinel lymph nodes were positive in 18.5% of PMBCs and 16% of MMBCs. Non-sentinel lymph nodes were positive in 14% of PMBCs and 39% of MMBCs. A micropapillary pattern was seen in 60% of LN positive PMBCs and 14% of LN negative PMBCs. Furthermore, 95% of PMBCs were ER(+), 84% were PR(+) and 9% were Her-2(+); 91% of MMBCs were ER(+), 87% were PR(+) and 33% were Her-2(+). Conclusions: PMBCs with a micropapillary pattern were more frequently associated with nodal disease. PMBCs with axillary disease had one or more of the following: micropapillary pattern, high nuclear grade, Her-2 positivity, smaller tumour size or younger age. Hence, axillary staging by sentinel lymph node biopsy is recommended in PMBCs.